Guardians of new spaces: "Home" and "exile" in Azar Nafisi’s Reading Lolita in Tehran, Marjane Satrapi’s Persepolis series and Azadeh Moaveni’s Lipstick Jihad - Hendelman-Baavur, Liora (Hagar: Studies in Society and Culture, 2008)
In this paper I explore the self-narrated life stories of Azar Nafisi, Marjane Satrapi and Azadeh Moaveni by focusing on "home" as a central metaphor. Each of these ltfe stories is embedded to a specific exilic experience of transmigration, which shaped the author’s perception of "home." A prominent characteristic of these autobiographical narratives, transmigration encompasses practices of circulating or commuting every few years between the country of origin and host countries, as well as maintaining cultural traditions and close connections with kinship networks. Drawing on real and imagined spaces called "home" as the frame of current discussion has two main purposes. First, it keeps the focus on how the concept and sense of home metaphorically change, rearticulated and reformulated across time and place. Second, it allows for elaboration of how transmigration obscures the contours of modern home and exile, thus constructing the former as temporal and portable.